Optical Coherence Tomography–Based Optimization of Mohs Micrographic Surgery of Basal Cell Carcinoma: A Pilot Study. Issue 4 (7th January 2013) - Wang, Katie Xiaoyi; Meekings, Adam; Fluhr, Joachim W.; McKenzie, Gordon; Lee, David A.; Fisher, Juliya; Markowitz, Orit; Siegel, Daniel M.
<x xml:space="preserve">Abstract</x> Background Optical coherence tomography (OCT) is a noninvasive imaging technique that uses a low‐power infrared laser to image up to 2 mm beneath the skin's surface. Objective To test the feasibility and diagnostic value of using in vivo OCT to define excision margins before Mohs micrographic surgery (MMS) of basal cell carcinoma (BCC). Methods Patients with biopsy confirmed BCC undergoing MMS were recruited (n = 52). Excision margins defined by experienced dermatologists were compared with those of OCT‐assessed borders and validated with histologic assessments. Results Forty‐one (79%) lesions were clear after one MMS procedure; 11 (21%) lesions required a second MMS stage after excision of the clinician‐predicted boundary. Generally, the OCT instrument indicated that the estimated clinical margin was 0.4‐mm larger than the OCT margin. For lesions requiring a single MMS stage, OCT indicated that lesions were 1.4 ± 1.3 mm smaller than the Mohs excision. Before excision of lesions requiring more than one MMS stage, OCT always indicated that the lesion boundary would extend outside the planned MMS defect boundary. Conclusions The present study shows the prospective utility of using OCT to refine clinically estimated borders for MMS. OCT assessment has the potential to reduce the excised area without compromising the integrity of tumor‐free borders.